The role of mindset in Japanese business and management - Isperdinova, Ж. И. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2018)
There are features of the national character of Japanese people, which can affect business and manage-ment in Japan. The purpose of this study is to analyze the impact of these features of the national character on the business environment and business management. To achieve this purpose, the author examined the historical roots of Japanese management, the main features of the national character of Japanese people, as well as the factors of their formation. The traits of Japanese national character can be divided into three groups: common ethnic characteristics, characteristics of group behavior, characteristics in everyday life. In addition, the author defined a concept of busi-ness culture and described the main characteristics of the Japanese way of doing business, such as the importance of interpersonal relationships, avoiding direct conflicts and disputes and the meaning of contracts. As a result of the analysis, we can see the connection between the features of the Japanese mentality and the business culture in Japan.